Attitudes Toward and Familiarity With Virtual Reality Therapy Among Practicing Cognitive Behavior Therapists: A Cross-Sectional Survey Study in the Era of Consumer VR Platforms - Lindner, Philip; Miloff, Alexander; Zetterlund, Elin; Reuterskiöld, Lena; Andersson, Gerhard; Carlbring, Per (Frontiers in Psychology, 2019)
Virtual Reality Exposure Therapy (VRET) is an efficacious treatment for fear and anxiety and has the potential to solve both logistic issues for therapists and be used for scalable self-help interventions. However, VRET has yet to see large-scale implementation in clinical settings or as a consumer product, and past research suggests that while therapists may acknowledge the many advantages of VRET, they view the technology as technically inaccessible and expensive. We reasoned that after the 2016 release of several consumer VR platforms and associated public acquaintance with VR, therapists’ concerns about VRET may have evolved. The present study surveyed attitudes toward and familiarity with VR and VRET among practicing cognitive behavior therapists (n=185) attending a conference. Results showed that therapists had an overall positive attitude toward VRET (pros rated higher than cons) and viewed VR as applicable to conditions other than anxiety. Unlike in earlier research, high financial costs and technical difficulties were no longer top-rated negative aspects. Average negative attitude was a larger negative predictor of self-rated likelihood of future use than positive attitude was a positive predictor and partially mediated the positive association between VRET knowledge and likelihood of future use, suggesting that promotional efforts should focus on addressing concerns. We conclude that therapist’s attitudes towards VRET appear to have evolved in recent years, and no longer appear to constitute a major barrier to implementing the next generation of VR technology in regular clinical practice.